Investigating the potential domino effect of a dazzling fiscal-period on CSR performance: a luxury brand scenario - Abhinav Karthikeyan Ravichandran; Rashmi Singh (International Journal of Corporate Social Responsibility (JCSR), 2024)
A consensus and buying pattern regarding luxury brands has endured a paradigm shift from being envied to being questioned or entirely overlooked. The pandemic has led to a fair share of economic implications. Brands are forced to watch their product range fully, except for reserving a portion of merchandise optimistic for brand jingoism. The study aims to quantify the impacts of financial metrics utilized to gain goodwill amidst an average consumer's mindset. A composite Corporate Social Responsibility (CSR) score represents the extent of a luxury brand's efforts in contributing to social and environmental concerns. The CSR score is hypothesized against these brands' financial and brand-value metrics. A Few Research questions are proposed on the same. A Panel-level analysis is undertaken to quantify the dependence and obtain insights. Relevant data is collected, with metrics identified from financial statements. The impacts of financial metrics and the firm's age on the CSR score are determined. While the Profit Margin, firm size, Tobin's Q, and Firm Age contribute positively to the CSR score, the firm's Return on Assets has a surprising negative influence. The impact of net income accrued is negligible, as inferred.
Keywords: 650; Brand value; Corporate social responsibility; Financial performances; Luxury brands